Challenges and Opportunities of Integrating Artificial Intelligence in Teaching and Learning in Secondary Schools in Gusau Educational Zone, Zamfara State - Sule Muhammad; Nura Umar Manya-Manya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examined the challenges and opportunities of integrating Artificial Intelligence (AI) in teaching and learning in secondary schools in Gusau Educational Zone, Zamfara State, Nigeria. The study was guided by three research objectives, three research questions, and three null hypotheses. A descriptive correlational survey research design was adopted. The population comprised teachers and students in public secondary schools within the study area, from which a sample of 384 respondents was selected using stratified and simple random sampling techniques. Data were collected using a researcher-developed structured questionnaire validated by experts. The reliability of the instrument was established using Cronbach's alpha, which yielded a coefficient of 0.89, indicating high internal consistency. Descriptive statistics (mean and standard deviation) were used to answer the research questions, while Pearson Product Moment Correlation and the independent-samples t-test were used to test the hypotheses at the 0.05 level of significance. The findings revealed a significant positive relationship between AI integration and teaching and learning opportunities (r = 0.62, p < .05), indicating that AI enhances instructional delivery, learner engagement, and access to educational resources. The study also found a significant negative relationship between implementation challenges and effective AI integration (r = −0.54, p < .05), suggesting that inadequate infrastructure, limited technical skills, and insufficient institutional support hinder successful AI adoption. Furthermore, a significant difference was observed in AI utilization between teachers and students (t = 4.85, p < .05), with teachers demonstrating higher levels of utilization than students. The study concluded that although AI has considerable potential to improve teaching and learning in secondary schools, its successful integration depends on adequate infrastructure, teacher capacity development, supportive educational policies, and equitable access to digital technologies.